1996
DOI: 10.1017/s0004972700015069
|View full text |Cite
|
Sign up to set email alerts
|

Higher commutators, ideals and cardinality

Abstract: For an associative ring R, we investigate the relation between the cardinality of the commutator [R, R], or of higher commutators such as [ [R, R], [R, R]], the cardinality of the ideal it generates, and the index of the centre of R. For example, when R is a semiprime ring, any finite higher commutator generates a finite ideal, and if R is also 2-torsion free then there is a central ideal of R of finite index in R. With the same assumption on R, any infinite higher commutator T generates an ideal of cardinalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…We cannot prove a complete generalisation of [8], but we are able to prove that if T is a finite higher commutator that generates an infinite ideal, and if the cardinality of such a T is minimal, then T must be a central subring with trivial multiplication. If there is an example of a finite T in a ring R generating an infinite ideal, then the c 2013 Australian Mathematical Publishing Association Inc. 0004-9727/2013 $16.00 direct sum of R with suitable matrix rings over finite fields would have a finite higher commutator generating an infinite ideal but neither central nor nilpotent.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…We cannot prove a complete generalisation of [8], but we are able to prove that if T is a finite higher commutator that generates an infinite ideal, and if the cardinality of such a T is minimal, then T must be a central subring with trivial multiplication. If there is an example of a finite T in a ring R generating an infinite ideal, then the c 2013 Australian Mathematical Publishing Association Inc. 0004-9727/2013 $16.00 direct sum of R with suitable matrix rings over finite fields would have a finite higher commutator generating an infinite ideal but neither central nor nilpotent.…”
Section: Introductionmentioning
confidence: 92%
“…In [8] we showed that for any finite higher commutator W in a ring R, the higher commutator [W, R] generates a finite ideal, denoted by ([W, R]). Thus the interest here is in higher commutators not of this form, although there seems to be no advantage in assuming this to start with.…”
Section: Since In Any Ringmentioning
confidence: 99%
See 3 more Smart Citations